Spatial analysis of the healthcare seeking behaviours of people with chronic health conditions during the COVID-19 pandemic in South Africa - Nkemdilim P. Anazonwu; Emeka E. Igboeli; Chukwuedozie K. Ajaero; Nneka Okafor; Ezinwanne E. Ezeibe; Casmir C. Mbaegbu; Ijeoma Ogu (Discover Public Health)
Abstract This study conducted a spatial analysis of the healthcare seeking behaviors of people with chronic health conditions during the COVID-19 pandemic across the nine provinces of South Africa. Data were sourced from the National Income Dynamics Study—Coronavirus Rapid Mobile Survey (NIDS-CRAM) of 2020/2021 which is a nationally representative panel survey of 7,000 South African individuals in all the nine provinces. The outcome variables were use of health facility and taking of COVID-19 test. Data analysis involved descriptive statistics, mapping, analysis of variance, and geographically weighted regression. While 22% of the respondents reported having chronic health conditions, 24% of the respondents visited health facilities during the COVID-19 pandemic. The results of the analysis of analysis of variance showed significant differences in the occurrence of chronic health conditions (F = 14.67; p = 0.000), testing for COVID-19 (F = 10.64; p = 0.000), and the use of health facilities (F = 16.01; p = 0.000) across the nine provinces of the country. The results of the geographically weighted regression (GWR) also indicated significant spatial variations on the influence of all the independent variables on the use of health facilities and on the proportion of respondents who took COVID-19 test. This study recommends the development and implementation of unique effective approaches related to the location-specific factors that influenced health seeking behaviors of people with chronic health conditions for each of the provinces.